Future-proofing workforce: high-skilled talent development strategies - Mohd Sharef, Nurfadhlina; Alli, Hassan; Wan Yahaya, Wan Aida (MBOT Publishing, 2024)
The rapid evolution of technology has necessitated a proactive response to future-proof the workforce. Despite being the driver of national digital economy, a concerted effort to collectively engage and report the voice of C-suite in future-proofing workforce has not been conducted. This paper synthesizes insights from the Malaysia Board of Technologists' forum, "Future-Proofing the Workforce: High-Skilled Talent Development Strategies." The imperative arises from the pressing need for nations and industries to adapt to the evolving technological landscape and ensure the readiness of their human capital. This paper advocates for strategic interventions, including identifying and quantifying current skill gaps, fostering collaboration between educational institutions and tech industries, coordinating competency development initiatives, formulating policies to attract and retain talent, promoting diversity, and implementing mechanisms to measure competency development. A strong emphasis is placed on the necessity of collaborative initiatives to shape Malaysia's future economy by cultivating a resilient, high-skilled workforce capable of propelling innovation, economic growth, and sustainable development in the digital era. These insights are designed to guide stakeholders in their endeavors to ensure the resilience and preparedness of Malaysia's workforce in the face of evolving technological and economic landscapes